Determining the required data elements to develop the information management system for Iranian traditional medicine - Razieh Mirzaeian; Abdolghader Bahraini; Hadi Kazemi-Arpanahi (BMC Complementary Medicine and Therapies)
Abstract Background Currently, there is no agreed-upon data collection tool for comprehensively structured documentation of Iranian traditional medicine (ITM) from the information management perspective. As ITM practice varies significantly from current medicine in diagnosis and treatment approaches, it is not appropriate to use data platforms or information systems developed for current medicine. Consequently, the collected data are non-comparable, reducing the verdicts’ generalization. Therefore, this research aims to create a minimum data set (MDS) for unified reporting of ITM diseases and interventions. Methods This multi-phased method study was performed from December 30, 2022 to March 20, 2023. The first phase involved a literature review, the second phase utilized the Delphi technique, and the third phase focused on validating the MDS-ITM. A list of potential data items was prepared after searching scientific databases, and grey literature, as well as reviewing existing information systems, forms, and websites related to ITM. A modified Delphi technique, including a two-round survey, was then employed. A panel of 34 individuals with clinical and research experience in ITM, was selected via purposeful sampling to rate the importance of candidate data items for inclusion in the ITM-MDS using a 5-point Likert scale. Items with an agreement level of 80% or more were deemed acceptable for inclusion in the final ITM-MDS. Finally, the content validity of the developed MDS was assessed using the content validity ratio (CVR) and content validity index (CVI) criteria. Results Consensus was reached on an ITM-MDS containing 291 items grouped into seven categories: Patient admission, past medical history, six principles of health preservation, objective signs, subjective symptoms, examination of body systems, and care plans. Conclusions The development of this MDS will enable ITM care settings  to exchange information and share resources more easily. It also provides an inclusive dataset and structured documentation of medical records. This MDS can contribute to delivering high-quality care and improving clinical decision-making.